PENGARUH LAMA PAPARAN LIPOPOLISAKARIDA (LPS) Phorpyromonas gingivalis SEBAGAI INDUKTOR PERIODONTITIS TERHADAP KADAR KOLESTEROL TOTAL TIKUS WISTAR (Rattus norvegicus) - Okky Dessy.R; Setyawati, Setyawati; Diena Fuadiyah (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
The chronic infections such as periodontitis that enters the body will activate various inflammatory mediators like TNFα IL5 and IL6. This will cause changes in the metabolism of fatty acids in the liver as well, as the expected increase in total cholesterol, triglycerides and LDL and lower HDL levels. These changes in lipid metabolism and atherosclerosis lesions so will increase the risk of coronary heart disease risk.The purpose of this study was to prove the effects of long exposure to lipopolysaccharide of P. gingivalis as induction periodontitis on cholesterol levels in Wistar rats.32 rats will be divided into three groups. Group 1 mice induced a LPS for 28 days while the group 2 induced a LPS for 60 days and the negative groups is a group of mice that were not treated. We are giving induction 3 times a week. Giving induction performed insivius intrasulkular on the teeth of the lower jaw then the sample will be identified on day 28 and 60. We will taking blood from the heart to measure total cholesterol levels. Total cholesterol measurement was conducted by elektrospektrofotometerik. Data were analyzed using ANOVA oneway and will be followed by post hoc multiple comparasion.Based on the statistical result showed that total cholesterol levels increased significantly in Wistar rats that had been induced by LPS P.Gingivalis, α < 0,05.Long exposure to LPS P.Gingivalis can increase total cholesterol levels inmale Wistar rats, but still need to do further research to see the effect of LPS from other bacteria on cholesterol levels of mice with the different experience.